The effect of parents' oral health behaviors on children and mutual communication. Issue 3 (December 2016) - Matsuo, Fumi; Sato, Shigemasa; Moriyama, Masaki
Abstract: Objectives: Interaction with a child influences that child's future oral health behavior. The influence garnered by a child's parents is especially important. This study measured the effect of parents' oral health behaviors on the child, and mutual communication among the family. Methods: Primary appraisal (interpretation of stressors) and secondary appraisals (analysis of the available resources) of parents and children were investigated to compare the evaluation of stress concerning oral health (based on the transactional model of stress and coping). A total of 377 families enrolled in all elementary schools in 2 cities (6 schools) were selected. Parent and child matching data were collected for children in 5th and 6th grade (10–12 years old) using separate questionnaires. The χ 2 test, t -test, and structural equation modeling were used for data analysis. Results: Data for 297 pairs of respondents were analyzed. There were no significant pathways for primary appraisal for the child. The final secondary appraisal model, and several global fit measures indicated good model fit. Child secondary appraisal was influenced only by mutual communication. The effect of communication on child secondary appraisal was significant, and the power of the effect (the square of the multiple correlation coefficient, R 2 ) was 7.3% (0.073). Conclusions: Results showed that increased communication between family members positively influenced children's understanding of oral health, and it was not influenced only by parental behavior toward the child's oral health. Dental professionals should approach parents about communication between family members to improve the self-management ability of children.